Methylmercury formation and sulfate-reducing bacteria in mine tailings - Winch, Susan (University of Ottawa (Canada), 2007)
Mercury (Hg) is a contaminant of global concern due to its toxicity to humans and other organisms. Methylmercury (MeHg) is the most hazardous form of mercury commonly found in the environment, as it bioaccumulates in aquatic food webs. Its production has been linked with microbial sulfate reduction in soils and sediments. Mine tailings cover vast land areas and release acidity and toxic metals, including Hg, to the environment. Sulfate-reducing bacteria (SRB) are active in mine tailings, indicating the potential for MeHg formation. This study investigated MeHg levels in mine tailings and the chemical and microbiological factors that might lead to significant MeHg contamination. Acidic base-metal tailings from northern Ontario were examined because they host active SRB but Hg and MeHg concentrations were unknown. Gold mine tailings from Nova Scotia were studied because Hg amalgamation was used there around 1860-1940, leaving Hg-rich tailings of unknown MeHg content and microbiology. MeHg accumulated in organic material in both environments. Acidic tailings contained negligible levels of MeHg, except for the Kidd Metsite tailings, which featured ≤ 12 nmol kg-1 MeHg in bulk tailings and 88 pM MeHg in porewaters, corresponding to a zone of sulfate reduction in the surficial layer (pH 3.7). Gold mine tailings featured a wide range of both HgT (0.2 - 53.5 mumol kg-1) and MeHg (< detection limit - 56.4 nmol kg-1). HgT levels decreased with distance from the stamp mills where ore was pulverized and treated with Hg. MeHg was influenced by multiple factors including HgT concentration, hydrological conditions, redox conditions, and demethylation. Seasonal fluctuations in MeHg were observed in one bog-type gold tailings dump. Analysis of DNA from MeHg-contaminated tailings and cultures detected Gram-positive (Firmicutes) and -negative (Deltaproteobacteria ) SRB in both types of tailings. A Deltaproteobacteria related sequence from the Kidd Metsite was unrelated to cultured lineages but 98-99% related to sequences detected in acid mine drainage elsewhere. This organism may be an important contributor to MeHg levels in acidic situations. DNA from gold tailings and cultures revealed a highly biodiverse bacterial community that included at least five Deltaproteobacteria spp. and sequences related to Hg-resistant genera.
Keywords: Environmental Sciences.